Penyebab Kurangnya Keaktifan Siswa SMP Hangtuah 1 Belawan dalam Pembelajaran PPKN Menimbulkan Nilai Rendah - Martua Felix Jonatan Simanullang; Bella Ayu Anzalia; Halimah Halimah; Pingky Monica Hasugian; Friska Lorentina Purba; Abdinur Batubara (Bersatu: Jurnal Pendidikan Bhinneka Tunggal Ika, 2024)
Pancasila and Citizenship Education (PPKN) is part of the Indonesian curriculum. PPKN aims to equip students with understanding and knowledge of the values ​​of Pancasila as the basis of Indonesian nationality and citizenship. In this lesson, besides introducing basic concepts such as democracy, human rights, and civic responsibility, you will also learn about Indonesian history, constitution, government systems, and culture. The research was conducted at SMP Hangtuah 1 Belawan. This research approach is based on a qualitative approach. The aim of this research is to comprehensively understand the phenomena experienced by research subjects and explain them in the form of scientific words and language. Students' lack of activeness in learning can be influenced by various factors. The factors most often found are factors that originate from outside the student (internal factors) and factors that originate from outside the student (external factors).